2017
DOI: 10.1002/pro.3339
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the large regulatory α subunit of phosphorylase kinase examined by modeling and hydrogen‐deuterium exchange

Abstract: Phosphorylase kinase (PhK), a 1.3 MDa regulatory enzyme complex in the glycogenolysis cascade, has four copies each of four subunits, (αβγδ) , and 325 kDa of unique sequence (the mass of an αβγδ protomer). The α, β and δ subunits are regulatory, and contain allosteric activation sites that stimulate the activity of the catalytic γ subunit in response to diverse signaling molecules. Due to its size and complexity, no high resolution structures have been solved for the intact complex or its regulatory α and β su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
3
5
0
Order By: Relevance
“…These results are consistent with a large body of evidence demonstrating that the β subunit undergoes significant conformational changes in the PhK complex . Differences in the HDX for the predicted (α/α) 6 barrels for the homologous α and β subunits provide additional evidence supporting differences in the modeled structures generated by us and others, with the barrel for α conserving more residues critical for GH catalytic function and that for β containing a small C‐terminal insert …”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…These results are consistent with a large body of evidence demonstrating that the β subunit undergoes significant conformational changes in the PhK complex . Differences in the HDX for the predicted (α/α) 6 barrels for the homologous α and β subunits provide additional evidence supporting differences in the modeled structures generated by us and others, with the barrel for α conserving more residues critical for GH catalytic function and that for β containing a small C‐terminal insert …”
Section: Resultssupporting
confidence: 88%
“…). Similarly, we recently demonstrated that predicted helices in the GHL catalytic domain of the homologous PhK α subunit exchanged moderately . This pattern was consistent with the simulated unfolding of a related GH‐15 family member that unexpectedly underwent thermal denaturation at moderate temperatures, suggesting the α subunit's predicted (α/α) 6 barrel to be moderately dynamic.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations